Parental doubts regarding childhood vaccinations after the COVID-19 pandemic: a qualitative study from Poland - Sandra Janiak; Elwira Piszczek; Krzysztof Buczkowski (Frontiers in Public Health)
BackgroundVaccinations are one of the most effective methods of preventing infectious diseases. Data published in recent years indicate a decline in routine childhood vaccination rates. Vaccine hesitancy is an increasingly serious problem, recognized as one of the 10 most significant threats to global health.ObjectThis study aims to identify the causes of parental hesitancy regarding childhood immunizations after the COVID-19 pandemic.MethodsWe conducted 33 in-depth interviews with parents who were hesitant to vaccinate their children. We analyzed the data using qualitative content analysis.ResultsThe main themes identified included concerns about adverse events following immunization, unsatisfactory communication with healthcare providers, distrust in the recommended vaccination schedule, individual risk assessment, conspiracy theories/anti-system sentiments, and organizational/financial barriers.ConclusionThe leading causes of vaccine hesitancy were fear of adverse events following immunization and unsatisfactory communication with healthcare professionals. These findings underscore the urgent need for improved training in communication, empathy, and negotiation skills among healthcare providers, along with the delivery of consistent, evidence-based vaccine information across all levels of care.